Case report: Robust response to sintilimab in advanced distal cholangiocarcinoma with PD-L1 expression and DNA damage repair - He, Wenguang; Song, Congcong; Ren, Jiwei; Ji, Xiao; Wang, Xiuyan; Liu, Lixia (Frontiers in Pharmacology, 2024)
Cholangiocarcinoma (CCA) is a highly heterogeneous tumor that occurs in the bile duct epithelium; adenosquamous carcinoma is a rare pathological subtype of CCA. The clinical treatment of patients with metastatic distal CCA poses significant challenges. We report a 53-year-old female diagnosed with a stage III adenosquamous carcinomas of distal CCA.Metastasis occurred 4 months postoperatively and she was diagnosed with stage IV disease. The patient was treated with Gemcitabine+Oxaliplatin (GP) and Capecitabine+Oxaliplatin (CAPEOX), followed by sintilimab monotherapy. After two cycles of treatment, the patient achieved partial response(PR) and the lesion continued to shrink. After 37 months of follow-up, the patient's liver metastasis had almost completely disappeared, and complete response (CR) was achieved.Moreover, she had more than 46 months of disease progression-free survival (PFS).Immunohistochemical testing showed high expression of PD-L1, and next generation sequencing revealed the presence of mutations in DNA damage repair (DDR) pathway genes. To the best of our knowledge, this is the first reported case of the successful treatment of metastatic distal adenosquamous CCA with sintilimab alone. Remarkably, patients of CCA with high PD-L1 expression and DDR pathway gene mutations may benefit from sintilimab treatment.